A Method to Accurately Predict Fatigue Life of Carbon Black‐Filled Natural Rubber Components Incorporating Self‐Heating Temperature - Li, Xiangxin; Mu, Longhai; Zheng, Dongju; Liu, Jinpeng; Song, Zongtao (Macromolecular theory and simulations, 2025)
Predicting the fatigue life of rubber components accurately has proven challenging, as existing methods often produce significant discrepancies compared to experimental results. This study presents a novel approach based on the combination of Abaqus and Endurica software, which can more accurately predict the fatigue life of rubber components, focusing on the impact of self‐heating. To address this, we took a Carbon Black‐Filled Natural lateral stop as an example, developed a thermo‐mechanical coupling approach that incorporates temperature‐dependent material parameters, derived by combining dynamic mechanical analysis tests and planar tension tests. This allowed us to capture the influence of temperature on the rubber's mechanical properties. Simulations incorporating self‐heating effects demonstrated remarkable accuracy, with a maximum deviation of 15.6% from experimental data. This is a significant improvement compared to simulations neglecting self‐heating, which exhibited a minimum deviation of 96.9%. This finding highlights the importance of considering self‐heating effects in fatigue life prediction of rubber components. This approach has the potential to significantly enhance the durability and performance of rubber components across various applications by enabling more accurate predictions, leading to improved component design and longer service life.